EFEKTIVITAS PERMAINAN PUZZLE TERHADAP PENINGKATAN SHORT TERM MEMORY PADA ANAK - Aisyah Nurfitriani; Elen Nofita Sari, Jelita Cahya Seruni, Rogers Clinton Pittor Halomoan, Vania Trisnawati, Wahyuning T (Adisam Publisher, 2024)
Short term memory is a place to store temporary memories such as what just happened or what the individual was thinking. The aim of this experiment is to determine whether or not there is an increase in short term memory through the experimental method with puzzle games. This experiment involved 10 students who matched the specified characteristics, namely students aged 7 years. The collection method uses kuasi eksperimental design dengan design one-group pre-test post- test. The results of data analysis were processed using the JASP (Jeffry's Amazing Statistics Program) Version 16. For Windows. The results of this experiment show that the results of the T-test carried out using the Student's T-test obtained a value of p = 0.001 < 0.05 which was declared significant. So, it can be said that changes occurred before and after treatment. Then, based on the output, it is known that the df value is 9, the value 0.05/2 is the same as 0.025, so the basic reference value for the t table is 2.262. Thus, the calculated t value is 4.583 > t table 2.262. It can be concluded that H0 is rejected, which means there is a significant effect on short term memory in children between before and after being given the puzzle game